THE DIRECT IMPACT THAT COVID-19 HAS ON NEUROLOGICAL IMBALANCES AND PSYCHOLOGICAL. - Dr. Ibrahim Safaa Kareem; Dr. Laith Ahmed Tuayen; Dr. Nadia Abdulkareem Hamdan (Scholar Express Journals, 2022)
This study aims to investigate the effect of COVID-19 on neurological and psychological disorders, as 100 patients were collected from Al-Hussein Teaching Hospital located in Thi-Qar Governorate - Iraq. The electronic record in the hospital was used for the purpose of determining information and demographic data for patients. The sample included both patients who had previously been diagnosed with mental disorders as well as patients whose mental disorders developed against the background of infection with the Coronavirus (delirium, neurocognitive disorders, neurological disorders, stress-related disorders). By adopting the statistical analysis program IBM SPSS SOFT, the MEAN± SD for the ages of the first group was (40.23 ± 7.7), while for the ages of the second group (43.2 ± 10.3) And the following results were found for patients with ischemic stroke (12%): plexus disorders (10%), in addition to (Mood disorder 18.9%) and (Parkinsonism18%), and statistical significance was found between the two groups with 0.001
Keywords: Haemorrhage; CV-19; mild; Severity